2022
DOI: 10.24127/poace.v2i2.2109
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Demokratis Dan Supervisi Akademik Kepala Sekolah Terhadap Kinerja Guru Di Sma Seputih Banyak

Abstract: Penelitian ini bertujuan untuk menjelaskan pengaruh langsung gaya kepemimpinan demokratis berpengaruh langsung terhadap kinerja guru di SMA Seputih Banyak,untuk menjelaskan pengaruh langsung supervisi akademik berpengaruh langsung terhadap kinerja guru di SMA Seputih Banyak, dan untuk menjelaskan pengaruh langsung gaya kepemimpinan demokratis dan supervisi akademik berpengaruh langsung secara simultan terhadap kinerja guru di SMA Seputih Banyak Seputih Banyak. Jenis penelitian yaitu Ex-Post Facto dengan teknik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other research highlights that the democratic leadership style of school principals has a positive and significant impact on employee performance (Sari et al, 2020). At Seputih Banyak High School, it was found that democratic leadership significantly improved teacher performance, confirming the importance of this leadership approach in the secondary school context ( (Rosida et al, 2022). This emphasizes the importance of the role of participative and inclusive leadership in improving the performance of school members, such as teachers, thereby creating a conducive and productive work environment.…”
Section: (Hypothesis 7 Is Accepted)mentioning
confidence: 82%
See 1 more Smart Citation
“…Other research highlights that the democratic leadership style of school principals has a positive and significant impact on employee performance (Sari et al, 2020). At Seputih Banyak High School, it was found that democratic leadership significantly improved teacher performance, confirming the importance of this leadership approach in the secondary school context ( (Rosida et al, 2022). This emphasizes the importance of the role of participative and inclusive leadership in improving the performance of school members, such as teachers, thereby creating a conducive and productive work environment.…”
Section: (Hypothesis 7 Is Accepted)mentioning
confidence: 82%
“…It was found that the democratic leadership style had a positive impact and had a significant effect on teacher performance at the Seputih Banyak Senior High School (SMA). Research results by (Rosida et al, 2022)emphasized that democratic leadership has been identified as the main factor that contributes positively to improving the performance of teachers in these educational institutions. This shows that the application of democratic principles in school leadership can create an environment that motivates and encourages active participation from teachers, thus having a direct impact on improving the quality of learning and teaching in these educational institutions.…”
Section: H 5 : Democratic Leadership Has a Positive And Significant E...mentioning
confidence: 99%